2015
DOI: 10.1373/clinchem.2015.238717
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Activating Estrogen Receptor 1 (ESR1) Mutations in Estrogen Receptor–Positive Metastatic Breast Cancer

Abstract: BACKGROUND Activating mutations in the estrogen receptor 1 (ESR1) gene are acquired on treatment and can drive resistance to endocrine therapy. Because of the spatial and temporal limitations of needle core biopsies, our goal was to develop a highly sensitive, less invasive method of detecting activating ESR1 mutations via circulating cell-free DNA (cfDNA) and tumor cells as a “liquid biopsy.” METHODS We developed a targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 40 publications
(30 reference statements)
3
140
0
Order By: Relevance
“…Most of these changes have been identified by comparing the plasma samples of specific cancers with that of healthy volunteers. Some examples include the alterations in estrogen receptor 1 and erb-b2 receptor tyrosine kinase 2 (ERBB2) of breast cancer patients which were not seen in tissues, but have been detected in cfDNA [79][80][81]. Uehiro and colleagues [82] compared the methylation signatures of nearly 140 candidate genes in plasma samples to detect early breast cancer in patients.…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
“…Most of these changes have been identified by comparing the plasma samples of specific cancers with that of healthy volunteers. Some examples include the alterations in estrogen receptor 1 and erb-b2 receptor tyrosine kinase 2 (ERBB2) of breast cancer patients which were not seen in tissues, but have been detected in cfDNA [79][80][81]. Uehiro and colleagues [82] compared the methylation signatures of nearly 140 candidate genes in plasma samples to detect early breast cancer in patients.…”
Section: Methods Targeting Druggable Mutation and Other Aberrations Imentioning
confidence: 99%
“…Accordingly, ddPCR monitoring of recurrent ESR1 mutations in cfDNA is a practical method to predict estrogen therapy response. Its higher sensitivity has been confirmed to have a detection limit of 0.05% [25] compared with 1% in multiplex allele-specific and realtime PCR [26] and 3.1% in NGS [27].…”
Section: Cancer Progression and Treatment Response Monitoringmentioning
confidence: 99%
“…Beyond ctDNA detection in the plasma of cancer patients in order to monitor disease dynamics, some groups were able to trace ctDNA mutations relevant to anticancer treatment resistance [38,39,40]. Murtaza et al [38] demonstrated in their study on 6 patients with advanced ovarian, breast and lung cancers that a high incidence of specific ctDNA alterations is associated with acquired drug resistance: A truncating mutation in the gene coding for mediator complex subunit 1 (MED1) was found in an MBC patient with progressive disease following treatment with tamoxifen and trastuzumab, and a splicing mutation in the growth arrest-specific 6 (GAS6) gene was identified in the same MBC patient following subsequent treatment with lapatinib.…”
Section: Ctdna As a Biomarker In Mbcmentioning
confidence: 99%